(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
In this article, the importance of the republican public opinion research center "Social Opinion" in the study and analysis of social processes in Uzbekistan is highlighted on the basis of analytical thinking.